Designing a field trip: The role of multiple intelligence and scientific reasoning. Issue 1 (March 2021) - Fadilloh, H; Rustaman, N Y; Sanjaya, Y
Abstract: Field trip is one learning method that provides direct experience for students to be able to interact with the surrounding environment. In Biology class, field trip is one of the keys when students want to observe natural phenomena. This study aim to identify student multiple intelligences and scientific reasoning profile as a reference in designing a field trip for high school students on ecosystem topics. The subjects in this study were 55 students from two classes of 10 th grade in even semester with purposive sampling. Data collection using Teen MIDAS (15-19 years) to identify student multiple intelligence and TOLT instruments for student scientific reasoning profile. The results of this study indicate that there are 3 types of intelligence that are most prominent, namely naturalistic, interpersonal and logical-mathematical as for future reference to dividing groups based on these three intelligences. In addition, student scientific reasoning which was found to be at 66% formal operation, 22% transitional and 12% concrete operation stage indicated that the design of the field trip that had to be prepared to have a level of analysis with one or two variables. There are still many students who have not been able to solve combinatorial reasoning. Thus it can be concluded that the best field trip design for this group of student is a design with worksheet that featured naturalistic, interpersonal and logical-mathematical with no more than two variables involved.